The Virtue of Opportunity: Moral Framing, Community, and Conditional Gentrification. (19th September 2021) - Ocejo, Richard E
Abstract: Gentrification is controversial mainly because of the potential displacement of existing low-income groups. Many gentrifiers therefore grapple with the moral implications of their role in this process. Based on three years of fieldwork and 46 interviews in a small city, this paper explains how gentrifiers construct the moral frames they use to identify and justify both themselves and gentrification as morally good, and how their moral ideas shape their behaviors. It argues that their own sense of community is the social source for their moral frame of opportunity, which they use to assign value to actors and actions based on whether they help realize the city's potential to revitalize, reduce poverty, and prevent displacement. This framing leads them either to support actors and actions behind "conditional gentrification" (i.e., gentrification they control) or oppose those who are against it. This paper shows how groups base justifications for morally questionable behavior on community, with strong implications for exacerbating inequalities.